Meningkatkan Keterampilan Memahami Puisi dengan Pendekatan Kontekstual Elemen Masyarakat Belajar Siswa Kelas X AK 1 SMKN 2 Buduran Kabupaten Sidoarjo - Susiana, Susiana (Center of Education Journal (CEJou), 2022)
The research is classroom action research (CAR) using 2 cycles and in each cycle using 4 stages. This study aims to improve the skills of understanding poetry by using a contextual approach to the learning community elements of class X AK 1 SMKN 2 Buduran, Sidoarjo Regency. This research is based on the results of low student learning scores so that it is necessary to develop an appropriate learning approach. One of the approaches used is the contextual approach. The data that has been obtained is then analyzed with a descriptive approach. The average score in the first cycle is 59.71% or has a poor category, while in the second cycle the average score is 71.29% or has a good value category. This shows that the application of a contextual approach to elements of the learning community can improve the skills of students in class X AK 1 at SMKN 2 Buduran, Sidoarjo Regency in understanding poetry.